ANTIBIOTIC-ASSOCIATED DIARRHEA AND CL. DIFFICILE-INFECTION IN CHILDREN: RISK FACTORS - L. N. Mazankova; S. G. Perlovskaya (LLC "Diagnostics and Vaccines", 2015)
The review of literature presents data on the incidence and characteristics of the current development of antibiotic-associated diarrhea (AAD) in children. Presented research materials of Russian and foreign scientists on risk factors activation toxigenic strains Cl. difficile, showed the relationship between the depth microecologi-cal metabolomical violations and Cl. difficile-infection in children.